Molar Dıstalızatıon Wıth Modıfıed 3d Bımetrıc Maxıllar Dıstalızatıon Arch - Sema Yüksel; Ayşe Gülşen; Tuba Tortop Üçem (Galenos Yayinevi, 1996)
The purpose of this study is to use "Rapid Maxillary Molar Distalization" in four case who had Class II malocclusion. Four females at ages of 11 to 12 were studied. Clinical and radiological observations following the distalization showed that the Class II molar relationship was corrected in 4-6 weeks; the maxillary molars distalized with mostly bodily movement; the anchorage of the maxillary incisors and mandibular molars was preserved; the mandibular incisors demonstrated a slight labial protrusion.